Comparative toxicity of ultrafine particles around a major airport in human bronchial epithelial (Calu-3) cell model at the air–liquid interface. (October 2020) - He, Rui-Wen; Gerlofs-Nijland, Miriam E.; Boere, John; Fokkens, Paul; Leseman, Daan; Janssen, Nicole A.H.; Cassee, Flemming R.
Abstract: Relatively high concentrations of ultrafine particles (UFPs) have been observed around airports, in which aviation and road traffic emissions are the major sources. This raises concerns about the potential health impacts of airport UFPs, particularly in comparison to those emitted by road traffic. UFPs mainly derived from aviation or road traffic emissions were collected from a location near a major international airport, Amsterdam-Schiphol airport (AMS), depending on the wind direction, along with UFPs from an aircraft turbine engine at low and full thrust. Human bronchial epithelial cells (Calu-3) model in combination with an air-liquid interface (ALI) cloud system was used for the in vitro exposure to UFPs at low doses ranging from 0.09 to 2.07 μg/cm 2 . Particle size distribution was measured. Cell viability, cytotoxicity and inflammatory potential (interleukin (IL) 6 and 8 secretion) on Calu-3 cells were assessed after exposure for 24 h. The biological measurements on Calu-3 cells confirm that pro-inflammatory responses still can be activated at the high cell viability (> 80%) and low cytotoxicity. By the Benchmark Dose (BMD) analysis, Airport and Non-Airport (road traffic) UFPs as well as UFPs samples from a turbine engine have similar toxic properties. Our results suggest that UFPs from aviation and road traffic in airport surroundings may have similar adverse effects on public health. Highlights: Airport and road traffic UFPs can activate inflammation in Calu-3 cells. Airport UFPs exert similar toxicity compared to UFPs from road traffic emission. ALI condition promotes cellular responses to particles at low exposed dose.